Deep phenotyping of an international series of patients with late‐onset dysferlinopathy. (1st April 2021) - Fernández‐Eulate, Gorka; Querin, Giorgia; Moore, Ursula; Behin, Anthony; Masingue, Marion; Bassez, Guillaume; Leonard‐Louis, Sarah; Laforêt, Pascal; Maisonobe, Thierry; Merle, Philippe‐Edouard; Spinazzi, Marco; Solé, Guilhem; et al.
Abstract: Background: To describe the clinical, pathological, and molecular characteristics of late‐onset (LO) dysferlinopathy patients. Methods: Retrospective series of patients with LO dysferlinopathy, defined by an age at onset of symptoms ≥30 years, from neuromuscular centers in France and the International Clinical Outcome Study for dysferlinopathy (COS). Patients with early‐onset (EO) dysferlinopathy (<30 years) were randomly selected from the COS study as a control group, and the North Star Assessment for Dysferlinopathy (NSAD) and Activity Limitation (ACTIVLIM) scores were used to assess functionality. Muscle biopsies obtained from 11 LO and 11 EO patients were revisited. Results: Forty‐eight patients with LO dysferlinopathy were included (28 females). Median age at onset of symptoms was 37 (range 30–57) years and most patients showed a limb‐girdle ( n  = 26) or distal ( n  = 10) phenotype. However, compared with EO dysferlinopathy patients ( n  = 48), LO patients more frequently showed atypical phenotypes (7 vs. 1; p  = 0.014), including camptocormia, lower creatine kinase levels (2855 vs. 4394 U/L; p  = 0.01), and higher NSAD ( p  = 0.008) and ACTIVLIM scores ( p  = 0.016). Loss of ambulation in LO patients tended to occur later (23 ± 4.4 years after disease onset vs. 16.3 ± 6.8 years; p  = 0.064). Muscle biopsy of LO patients more frequently showed an atypical pattern (unspecific myopathic changes) as well as significantly less necrosis regeneration and inflammation. Although LO patients more frequently showed missense variants (39.8% vs. 23.9%; p  = 0.021), no differences in dysferlin protein expression were found on Western blot. Conclusions: Late‐onset dysferlinopathy patients show a higher frequency of atypical presentations, are less severely affected, and show milder dystrophic changes in muscle biopsy. Abstract : Late‐onset dysferlinopathy patients show a higher frequency of atypical presentations, including camptocormia, and are less severely affected compared with early‐onset patients. Furthermore, they present less necrosis and inflammation in muscle biopsy.